Death is a Tragic Theme in The New Iraqi Novel Anton Sinan’s The Pomegranate Tree Alone as model - al-Shawabkieh, sumaya (Dirasat: Human and Social Sciences, 2019)
This study attempts to describe the domain of the new post-2003 Iraqi novel, which constitutes a record of the profound Iraqi wound as it documents the occupation, terrorism, and sectarian fighting following the fall of Baghdad in 2003 and its images of free death and ruin. It is a form which relates current aspects of violence, extremism, and the formation of a new identity on the level of form and content. This study explores the representations of death in The Pomegranate Tree Alone by Iraqi novelist, Antoine Sinan. It investigates its physical and moral apparitions, as well as its implications on the novel’s structure being an abstract theme of tragedy that casts a shadow over all aspects of the novel. The study examines the extent to which the novelist has succeeded in employing this tragic theme in an artistic form that differs from the traditional one. Sinan’s is a form made richer by references, allusions, and signifying aesthetics.